Two Hitherto Little-Studied Turkish Translations by Wojciech Bobowski alias Albertus Bobovius - Neudecker, Hannah (Oriens, 2017)
In this contribution, I will discuss two Turkish translations made by the famous Ottoman court official, Wojciech Bobowski, alias Albertus Bobovius (d. ca. 1677 CE). One is his translation of the Anglican Catechism (1654), the other his version of the Ianua linguarum by Johannes Amos Comenius (Komenský, 1592–1670), the Czech philosopher, pedagogue and theologian (1658). Both texts have only survived as manuscripts and neither has been studied in any depth before. I will present the texts, as well as their historical backgrounds, and shed some new light on the life of the translator as well.